E-professionalism and health-care professionals - Kavya Ganesh Kamaraj; Girish R Shavi; Shankar Shanmugam; Senthil Kumar Sennan; Gunasekaran Lalithambigai; Jennifer Monisha Rajan (Wolters Kluwer Medknow Publications, 2023)
The fast rise and widespread use of online social networking platforms, which are accessed by millions of people, provide significant ethical and professional issues for practitioners. The usage of online social networking forums has grown in popularity, particularly across the younger generation of physicians and patients. To find the most recent literature regarding this subject, the present review made the use of Web of Science, PubMed (Medline), and Google Scholar (as a search engine). The searches were conducted using the following search terms: professionalism, social media, social networks, Internet, Web 2.0, eHealth, Facebook, Twitter, Instagram, TikTok; included in the title or abstract or keywords. The search was restricted to studies published in English from 2009 to 2021. In this article, we explore the ethical issues that have arisen as a result of the increased usage of online social networking platforms in the patient-doctor interaction as well as the way these social media tools can be equipped for the improvement of health education and health care.